Aeschylus's Suppliant Women : The Tragedy of Immigration - Bakewell, Geoffrey W. (Book collections on Project MUSE., 2013)
This book offers a provocative interpretation of a relatively neglected tragedy, Aeschylus's Suppliant Women. Although the play's subject is a venerable myth, it frames the flight of the daughters of Danaus from Egypt to Greece in starkly contemporary terms, emphasizing the encounter between newcomers and natives. Some scholars read the play as modeling successful social integration, but here, the author argues that the play demonstrates, above all, the difficulties and dangers noncitizens brought to the polis.